The Influence of Korean Wave and Korean Idol Brand Ambassadors on Skincare Purchase Intention : (A Study on Undergraduate Management Students at Universitas Dharma Andalas) - Adelia Fanisa; Puti Embun Sari (Management Institute Faculty of Economics Universitas Andalas, 2026)
This study aims to analyze the influence of the Korean Wave and Korean idol brand ambassadors onpurchase intention toward skincare products among undergraduate Management students atUniversitas Dharma Andalas. This study uses a quantitative approach with a causal research design.The sample consists of 130 respondents selected using purposive sampling. Data were collected throughquestionnaires using a Likert scale and analyzed using multiple linear regression with SPSS. Theresults show that the Korean Wave has a positive and significant effect on purchase intention (sig.0.004). Korean idol brand ambassadors also have a positive and significant effect (sig.0.000) and are themost dominant variable. Simultaneously, both variables significantly influence purchase intention(sig. 0.000) with a coefficient of determination (R²) of 57.4%.